Pengaruh Kepemimpinan Visioner Kepala Sekolah, Motivasi Kerja, Kompetensi Pedagogik Terhadap Kinerja Guru Taman Kanak-Kanak - Siti Fariha (Jurnal Syntax Transformation, 2023)
This study generally aims to analyze the influence of the principal's visionary leadership, work motivation and teacher pedagogic competence on the performance of Kindergarten teachers in Batu Ceper District, Tangerang City, while specifically, this study aims to determine and obtain empirical data regarding the influence of: 1) visionary leadership on teacher work motivation. 2) visionary leadership on teacher pedagogic competence. 3) teacher's work motivation on teacher pedagogic competence. 4) visionary leadership on teacher pedagogic competence. 5) Teacher work motivation on teacher pedagogical competence. 6) teacher's pedagogical competence on teacher performance. The approach used is quantitative using causal survey techniques with path analysis methods. The sample in this study is the same as the reachable population, namely 87 teachers. consists of 19 Kindergartens in the Batu Ceper sub-district, Tangerang City. The results of the analysis Based on the results of the study it can be concluded as follows: 1) There is a positive and significant influence of visionary leadership on the work motivation of Kindergartens in the Batu Ceper District, Tangerang City. 2) there is a positive and significant influence of visionary leadership on the work motivation of kindergarten teachers in Batu Ceper District, Tangerang City. 3) there is a positive and significant effect of work motivation on the pedagogic competence of kindergarten teachers in Batu Ceper District, Tangerang City. 4) there is a positive and significant influence of visionary leadership on the performance of kindergarten teachers in the Batu Ceper District, Tangerang City. 5) there is a positive and significant effect of work motivation on the performance of kindergarten teachers in Batu Ceper District, Tangerang City. 6) there is a positive and significant effect of pedagogical competency on the performance of kindergarten teachers in Batu Ceper District, Tangerang City.